(untitled) (Revista de Ciências Agroveterinárias, 2012)
This paper describes an atypical case of myeloid leukosis that occurred in an adult Black Rock hen that lived in a backyard chicken flock. The bird showed interruption of egg production, weight gain, and pelvic limb paresis. At necropsy, multiple whitish friable nodules were observed on the skin, subcutaneous, muscles, sternum, synsacrum, trachea, lung, bone marrow, liver, kidneys; besides enlarged liver, spleen and kidneys. Histopathology showed the proliferation of neoplastic round cells with vesicular eccentric nuclei and enlarged cytoplasm containing eosinophilic granules. These findings are compatible with myeloid leukosis.